The relationship between Geographical Information System (GIS) quality and user satisfaction, and its influence on individual work performance / Mohd Saiful Rahman ... [et al.] - Rahman, Mohd Saiful; Mohamed Shuhidan, Shamila; Masrek, Mohamad Noorman; Baharuddin, Mohammad Fazli (Faculty of Information Management, 2024)
The measurement of software quality has always been subjective. Many theories and models were developed to identify the contributing factors in software quality. This study focuses specifically on Geographical Information Systems (GIS) quality. The impact given by GIS enlightens decision-makers through the location element. This study focuses on the aspects of GIS quality according to the ISO-25010 software quality model. The aim of this study is to identify the level of GIS quality, user satisfaction, and individual work performance in the selected organization. It also aims to investigate the relationship between GIS quality and user satisfaction as well as examining the influence of user satisfaction on individual work performance. A total of 362 respondents have given responses to the study, where all findings were collected, reviewed, and analyzed. From the analysis, it is found that from 10 hypotheses, seven (7) are supported and three (3) are not.